Terapi Laser untuk Skar Hipertrofik dan Keloid - Santoso, Ritchie; Kurniawati, Yuli; Diba, Sarah; Rusmawardiana, Rusmawardiana; Nopriyati, Nopriyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aim to evaluate the success rate of laser therapy in hypertorphic, and keloid scar patients based on scar characteristics. The research method used is systematic review using data from Pubmed, Cochrane Library, Clinicaltrials.gov, and Mendeley from 1994 to July 2022. The results found a total of 28 studies, consisting of 3 retrospective studies, 5 randomized controlled trials (RCT), and 20 prospective studies included in the review. This research evaluated 11 585nm pulse dye laser (PDL) studies, 2 595nm PDL studies, 3 1064 nm Nd:Yag studies, 3 1550nm Er:Yag studies, 3 2940nm Er:Yag studies, and 6 10,600nm fractional CO2 laser studies. In conclusion, the 585 nm pulse dye laser showed the best overall therapeutic success rate. Fractional CO2 10,600nm, Er:YAG 2940nm, and Nd:YAG 1064nm lasers showed the best therapeutic response for reducing erythema, pigmentation, height, and scar consistency. Further research is needed to assess the success rate of therapy. Keyword: Keloid, Laser, Hypertrophic scar, Systematic Review